OPPORTUNITIES TO USE INTERNATIONAL STANDARDS OF FINANCIAL REPORTING IN THE PROCESS OF TRANSITION TO A GREEN ECONOMY IN SERVICE COMPANIES (Marketing Journal, 2025)
This article analyzes the possibilities of using international standards of financial reporting in service enterprises in the process of transition to a green economy. The practical advantages of such advanced approaches as GRI, ESG, IFRS S1/S2 and TCFD fo r the service sector are revealed. Based on foreign experience, proposals are developed to ensure environmental transparency and sustainable development through financial reporting in the conditions of Uzbekistan.
Keywords: Green economy; service sector; financial reporting; international standards; IFRS S1/S2; GRI; ESG; TCFD; sustainability reports; Uzbek experience